High Speed Rail System and the Tourism Market: Between Accessibility, Image and Coordination Tool - marie delaplace; sylvie bazin; francesca pagliara; Antonio Sposaro (European Regional Science Association (ERSA), 2014)
the aim of this P is to propose a state-of-the-art concerning the interaction between High-Speed Rail systems and the tourism market, in order to identify the possible best practices aiming to enhance the value of the tourist activities. This question arises because there are many projects of High-Speed Rail and others are ongoing, whose economic justification is based on the benefits deriving from them. In November 2013 there were 21.472 km of High Speed Railways (i.e., whose speed is greater than 250 km / h) in the world, 13964 km were under construction and 16347 km were scheduled by 2025. In 2025, 51784 km should be operational (UIC 2013), as in Germany, Belgium, Brazil, China, the United States, France, Iran, Morocco, and Portugal. Because of increase in accessibility, which the territories served benefit, the actors involved expect a dynamic economy, in general, and of the tourism in particular. Although expectations are important in France as abroad, a literature review of studies carried out ex-post shows that the effects are not systematic. Indeed, there is not a systematic dynamism because of the implementation of the High-Speed service. More specifically, we show that different types of tourism are variously impacted by High-Speed Rail service. Urban and business tourism are the most impacted ones. Specifically, we show the importance of the prior existence of famous cities. These last ones must offer a basket of tourist products and services that benefit a good accessibility from being served by a High Speed Rail station. But it can be noted also that, if the high speed allows, in some circumstances, the increase in the number of tourists, a decrease of stay is also possible. Moreover, as the number of cities served by High Speed Rail increases, High Speed Rail can be itself a differentiation asset to develop tourism market. The role of high speed should also be related to accessibility, understood both as attractiveness of the destination such as coordination of the actors in order to propose a coordinated and renewed supply.
Keywords: L83; R40; R50; R58; 330; Tourism; High Speed Rail; local economic development